Technological and probiotic characterisation of Lactobacillus casei / paracasei strains and their phage resistant mutants - Capra, María Luján (2014)
Technological, biological and functional attributes of two groups of spontaneous bacteriophage-resistant mutants were investigated to verify features similar to those of their respective phage-sensitive parent probiotic strains (Lactobacillus casei/paracasei). A derivative from each group was challenged with phages in simulated probiotic product fermentation. Technological performance, compared with the original strains, was demonstrated. Minimal variations were detected in acidifying and enzymatic profiles. No β-glucuronidase activity was observed, but very high α-glucosidase and β-galactosidase activities were recorded. Low proteolytic activities and inability to ferment prebiotics were observed. Within one group, significant differences throughout simulated gastrointestinal-transit were observed. Neither of the strains deconjugated bile salts, but all showed inhibitory activity against four pathogens. Both mutants increased IgA-producing cell numbers in vivo in a manner similar to that of the parent strains. Two derivatives demonstrated improved phage-resistance phenotype compared with the parental strains, resulting in alternatives for industrial rotation schemes.